2010
DOI: 10.4028/www.scientific.net/kem.450.63
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity Influence Research on Load Capacity of Heavy Hydrostatic Bearing

Abstract: Lubricant viscosity is one of the key parameters in hydrostatic bearing research. In order to solve the load capacity of hydrostatic bearing in the heavy equipment, viscosity-temperature equation of lubricant film is established, and the viscosity-temperature curve is fitted by B-Spline curve. Finite volume method is used on numerical simulation of pressure field of heavy hydrostatic bearing in constant and variable viscosity respectively and in different rotational velocity, whereafter, viscosity influence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…In earlier studies, also (3, 3), (10, 8), and (11, 9) maser emission has been reported (Mauersberger et al 1987;Zhang & Ho 1995). The (6, 3) line, which 25 years ago also contributed to the 54.5 km s −1 group of masers (Madden et al 1986), is now seen at ∼57 km s −1 (see above).…”
Section: Variability On Long Time Scalesmentioning
confidence: 76%
See 2 more Smart Citations
“…In earlier studies, also (3, 3), (10, 8), and (11, 9) maser emission has been reported (Mauersberger et al 1987;Zhang & Ho 1995). The (6, 3) line, which 25 years ago also contributed to the 54.5 km s −1 group of masers (Madden et al 1986), is now seen at ∼57 km s −1 (see above).…”
Section: Variability On Long Time Scalesmentioning
confidence: 76%
“…Figures 6 and 7 show spectra of ammonia lines with maser features being closer to the quasi-thermal "systemic" emission peaking near 60 km s −1 . Interestingly, the (3, 3) and (10, 8) lines, previously reported to exhibit maser emission at ∼54 km s −1 (Mauersberger et al 1987;Zhang & Ho 1995), now show exclusively the quasithermal 60 km s −1 component (Fig. 8).…”
Section: The Spectramentioning
confidence: 97%
See 1 more Smart Citation
“…(Figure 14). In addition, there are several compact and UCH II regions that are not detected at <20µm because of heavy extinction (Gaume et al 1993;Zhang & Ho 1995.…”
Section: Sed Models For Mysosmentioning
confidence: 99%
“…The region shows widespread NH 3 thermal emission (Zhang & Ho 1997) as well as strong maser emission from OH, CH 3 OH, H 2 O, and NH 3 (Zhang & Ho 1995;Imai et al 2002;Fish & Reid 2007;Etoka et al 2012;Surcis et al 2012).…”
Section: Introductionmentioning
confidence: 99%